Sub-MICs of Mentha piperita essential oil and menthol inhibits AHL mediated quorum sensing and biofilm of Gram-negative bacteria - Husain, Fohad M.; Ahmad, Iqbal; Khan, Mohammad S.; Ahmad, Ejaz; Tahseen, Qudisa; Khan, Mohd Shahnawaz; Alshabib, Nasser A. (Frontiers in Microbiology, 2015)
Bacterial quorum sensing (QS) is a density dependent communication system that regulates the expression of certain genes including production of virulence factors in many pathogens. Bioactive plant extract/compounds inhibiting QS regulated gene expression may be a potential candidate as antipathogenic drug. In this study anti-QS activity of peppermint (Mentha piperita) oil was first tested using the Chromobacterium violaceum CVO26 biosensor. Further, the findings of the present investigation revealed that peppermint oil at sub-MICs strongly interfered with acyl homoserine lactone (AHL) regulated virulence factors and biofilm formation in Pseudomonas aeruginosa and Aeromonas hydrophila. The result of molecular docking analysis attributed the quorum sensing inhibitory activity exhibited by peppermint oil to menthol. Assessment of ability of menthol to interfere with quorum sensing systems of various Gram-negative pathogens comprising diverse AHL molecules revealed that it reduced the AHL dependent production of violacein, virulence factors and biofilm formation indicating broad-spectrum anti-QS activity. Using two E. coli biosensors, MG4/pKDT17 and pEAL08-2, we also confirmed that menthol inhibited both the las and pqs quorum sensing systems. Further, findings of the in vivo studies with menthol on nematode model Caenorhabditis elegans showed significantly enhanced survival of the nematode. Our data identified menthol as a novel broad spectrum quorum sensing inhibitor.